The Impact of Water Supply on the Quality and Health of Potato - Kruppa, József; Sárvári, Mihály; Zsom, Eszter (Acta Agraria Debreceniensis, 2003)
Besides its effect on potato yield, water also has a significant impact on yield quality. Excess water (too much precipitation, over-irrigation) and the lack of water (lack of precipitation or irrigation) both trigger stress in the plant and can significantly worsen the quality of the yield (seed potato) and deteriorate the health of the plant and the seed potato. Excess precipitaton or irrigation water leaches nitrate-nitrogen under the rhizosphere, consequently, the amount of available nitrogen decreases leading to the deficiency of N in potato. If water cover (the maximally saturated state of soil) exceeds 8-12 hours, it can cause root destruction (because of the lack of oxygen), which leads to the wilting and later to the death of the plant. Abundance of water caused by excess precipitation or irrigation is a major problem primarily on sandy loam, loam and clay loam soils with bad structure and water management qualities, but also on any soils, which are over-irrigated or irrigated at an improper time. Symptoms of the lack of water are detectable mostly when the available water content of the soil (disponible water) decreases under 60-65%.In the present year, there was a lack of precipitation on the Great Plain, which can be compensated by proper irrigation. Unfortunately, this problem is further intensified by the high temperature, which results in faster ripening and accompanied with fluctuating soil moisture content, in the formation of secondary tubers.